Hubungan Pengetahuan Dengan Sikap Perawat Terhadap Perawatan Paliatif Di Rumah Sakit Umum Daerah Harapan Dan Doa Kota Bengkulu - Qurratul A’yuni; Sasteri Yuliani; Murwati Murwati (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Palliative care is an approach that aims to improve the quality of life of patients with chronic and terminal illnesses. Nurses' knowledge and attitudes are important factors in the success of palliative care services. This study aims to determine the relationship between nurses' knowledge and attitudes towards palliative care at the Harapan dan Doa Regional General Hospital in Bengkulu City.This study used a descriptive analytical cross-sectional design. The sample consisted of 35 nurses working in the ICU, haemodialysis unit, and Madinah unit, selected using total sampling. The research instruments were questionnaires on nurses' knowledge and attitudes towards palliative care. Data analysis was performed using univariate and bivariate analysis with the chi-square test.The results showed that most nurses had good knowledge of palliative care (77.2%) and a positive attitude (68.6%). The majority of nurses also practised palliative care at a high level (91.4%). The chi-square test yielded a p-value of 0.004 for the relationship between knowledge and practice, and a p-value of 0.028 for the relationship between attitude and practice, which means that there is a significant relationship between nurses' knowledge and attitude towards palliative care.The conclusion of this study is that nurses' knowledge and attitudes play an important role in supporting palliative care practices. It is recommended that training, seminars, and continuing education be provided so that all nurses have equal knowledge and positive attitudes, thereby optimising the quality of palliative care services in hospitals.